Business Disruptions, Financial Fragility and Resilience Strategy: Exploration of Impact of The Covid-19 on Micro, Small and Medium Entreprises - Sari Surya (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
The Covid-19 pandemic has impacted the world economy, including Micro, Small, and Medium Enterprises (MSMEs). This study aims to find out how the conditions of MSMEs during the Covid-19 pandemic, which led to business disruptions and financial fragility in most of the MSMEs in Indonesia. Are MSMEs able to survive in an uncertain economic situation, or will they give up by closing their business forever or looking for new business strategies? This research was conducted with a qualitative approach and data obtained from semi-structured interviews with MSMEs in Padang City, Indonesia. Data was analyzed with Content Analysis. The findings reveal several main themes related to business disruptions, financial fragility, and resilience strategy. The central theme related to business disruption is the creation of obstacles resulting from the Covid-19 pandemic. Meanwhile, the central theme of financial fragility is about the adequacy of cash to run a business. Finally, a theme related to the resilience strategy is the importance of adaptation. Although most of these MSME businesses experienced a decline in business, several sectors experienced increased demand and sales, especially those related to necessities, health and hygiene products.